Explicit and Contextual Vocabulary Intervention: Effects on Word and Definition Learning. (12th May 2021) - Antia, Shirin D; Catalano, Jennifer A; Rivera, M Christina; Creamer, Catherine
Abstract: Two single-case studies examined the effects of a vocabulary intervention on K-second grade Deaf or Hard-of-Hearing (DHH) children's vocabulary learning. The intervention consisted of (a) explicit instruction that included fast mapping, and drill and practice games and (b) in-context activities that included book reading, conceptual activities, and conversation. Study 1 compared the effectiveness of in-context alone and explicit+in-context instruction for four DHH children. This multiple baseline across content study showed that children learned more words rapidly in the explicit + in-context condition. Study 2 examined the effects of the explicit+in-context intervention on five DHH children's word and definition learning and use of new words in spontaneous communication. A multiple baseline study across participants showed that all children learned the targeted vocabulary, improved expression of definitions, and used target words in spontaneous language. We discuss the value of explicit and in-context instruction on breadth and depth of vocabulary learning.